IMPROVING LEARNING ACHIEVEMENT THROUGH INTERPERSONAL INTELLIGENCE AND SELF-REGULATED LEARNING - Retno Purwitasari; Mardi Mardi; Ayatulloh Michael Musyaffi (International Journal of Multidisciplinary Research and Literature, 2023)
The material in accounting computer lessons utilizes technology to present problems to students. Thus, generating differences in student achievement based on various factors and investigating the relationship between student success and factors such as interpersonal intelligence and self-regulated learning. This study uses a survey method based on a quantitative approach. The Affordable population of this study is the eleventh-grade students in the Department of financial accounting SMKN Jakarta with 174 students. Simple random sampling is used as a sampling technique. The sample was taken randomly without certain criteria so that students with high or low achievement could be a research sample. Known results of this study's average (mean) student achievement into Category B (Good). Furthermore, students with interpersonal intelligence and self-regulated learning are in the "low" and "high" categories. In this study, teachers as educators in schools can guide and train students 'social relationships by forming study groups regularly so that students can improve interpersonal relationships with other students, besides that students can understand each other's learning needs to form learning strategies that will produce learning goals to be achieved. The findings of this study stated that there is a positive relationship between computer accounting learning achievement of vocational school students with interpersonal intelligence and self-regulated learning